2018
DOI: 10.1139/cjas-2016-0232
|View full text |Cite
|
Sign up to set email alerts
|

Using body measurements to estimate body weight in gilts

Abstract: The absence of a scale on pig farms has led to indirect body weight (BW) estimation using regression models based on body measurements. The objectives of the present study were to (1) develop prediction equations for weight estimation in gilts using body measurements (FF: flank-to-flank distance; L: length; HG: heart girth; BF2: ultrasound backfat measurement; LD: loin depth; and BCS: body condition score) and (2) validate the use of an existing prediction equation for BW in gilts (HG2 × L × 69.3 = HGLW), only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Although information on gilt weight at either the onset of boar stimulation, or at the time of pubertal estrus, is a critical step in meeting target gilt breeding weights [49], these records are typically not available across the production industry today [90]. Although a weigh scale is the most accurate way to determine body weight, estimating body weight using a weight tape that is established on the basis allometric growth curves which take advantage of the high correlation between heart girth circumference and body weight, is an objective and simple to manage alternative [90,91].…”
Section: Appropriate Management Of Weight Physiological Maturitymentioning
confidence: 99%
“…Although information on gilt weight at either the onset of boar stimulation, or at the time of pubertal estrus, is a critical step in meeting target gilt breeding weights [49], these records are typically not available across the production industry today [90]. Although a weigh scale is the most accurate way to determine body weight, estimating body weight using a weight tape that is established on the basis allometric growth curves which take advantage of the high correlation between heart girth circumference and body weight, is an objective and simple to manage alternative [90,91].…”
Section: Appropriate Management Of Weight Physiological Maturitymentioning
confidence: 99%
“…An animal-based measure of CSIA includes a spatial (mass) allowance such that 90% of pigs can lie down at once in group pens and that sows can lie down fully in stalls. Studies have shown promise and commercialization in the area of extracting the 3D shape of pigs for automatic mass and weight estimations [35,114,115,116].…”
Section: Summary Of Remote Monitoring Technology Applications For mentioning
confidence: 99%
“…While animal biometrics is an emerging field focused on quantification and detection of the phenotypic appearance of species, individuals, behaviors, and morphological traits ( Kühl and Burghardt, 2013 ), animal morphometrics ( Rohlf, 1990 ; Adams et al, 2004 ; Doyle et al, 2018 ) is almost exclusively focused on landmark-based methods (and less on outline-based methods) using quantitative analysis of form relying on measuring the size and shape of animals, and the relation between size and shape (allometry). Estimation of livestock BW using biometric and morphometric measurements has been studied in detail for various species, such as cattle ( Taşdemir et al, 2011a , b ; Miller et al, 2019 ; Tasdemir and Ozkan, 2019 ; Gjergji et al, 2020 ; de Moraes Weber et al, 2020 ; Rudenko, 2020 ), pigs ( Brandl and Jørgensen, 1996 ; O’Connell et al, 2007 ; Mutua et al, 2011 ; Sungirai et al, 2014 ; Al Ard Khanji et al, 2018 ), sheep ( Eyduran et al, 2015 ; Huma and Iqbal, 2019 ), goats ( Sebolai et al, 2012 ; Eyduran et al, 2017 ; Temoso et al, 2017 ), camels ( Fadlelmoula et al, 2020 ; de Moraes Weber et al, 2020 ), yaks ( Yan et al, 2019 ), poultry ( Mendeş and Akkartal, 2009 ), and fish ( Fernandes et al, 2020b ). This process is typically applied to avoid drawbacks associated with manually performed individual animal weighing such as: 1) the animal and manual laborer stress associated with animal relocation, 2) the costs associated with this labor-intensive process, and 3) the significant cost associated with acquiring and maintaining industrial scales.…”
Section: Biometric and Morphometric Measurements For Bw Predictionmentioning
confidence: 99%
“…Some of the most popular morphometric measurements include heart girth circumference, wither height, hip width/height, and body length. These measurements are manually selected and used as features for traditional regression models, which result in predictive equations with one or more variables based on the number of selected measurements in various species, such as cattle ( Heinrichs et al, 1992 ; Franco et al, 2017 ; Goopy et al, 2018 ), pigs ( Groesbeck et al, 2002 ; Mutua et al, 2011 ; Sungirai et al, 2014 ; Al Ard Khanji et al, 2018 ), sheep ( Sowande and Sobola, 2008 ; Kunene et al, 2009 ; Chay-Canul et al, 2019 ; Canul-Solis et al, 2020 ), goats ( Sebolai et al, 2012 ), camels ( Fadlelmoula et al, 2020 ; Meghelli et al, 2020 ), and yaks ( Yan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%